2018
DOI: 10.3390/ijerph15112469
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Diets in Rural Victoria—Cheaper than Unhealthy Alternatives, Yet Unaffordable

Abstract: Rural communities experience higher rates of obesity and reduced food security compared with urban communities. The perception that healthy foods are expensive contributes to poor dietary choices. Providing an accessible, available, affordable healthy food supply is an equitable way to improve the nutritional quality of the diet for a community, however, local food supply data are rarely available for small rural towns. This study used the Healthy Diets ASAP tool to assess price, price differential and afforda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 30 publications
9
49
0
1
Order By: Relevance
“…Consistent with similar surveys, particularly in Australia where the GST of 10% is not applied to basic, healthy foods [22,23,24,25], application of the Aboriginal and Torres Strait Islander Healthy Diets ASAP methods in remote Aboriginal communities showed that a healthy diet ($AUD827.63) was less expensive than the current diet ($AUD1,023.16) per household per fortnight. However, at 76% of the cost of the current diet, a healthy diet was potentially more affordable in the remote Aboriginal communities studied than in other places, where the cost of the healthy diet ranges between 80–85% [22,23,24,25]. Surprisingly, this price differential between the current and healthy diets was larger than in other studies even though alcohol was not included in the current diet, as the communities are ‘dry’ and alcohol is not available for sale.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with similar surveys, particularly in Australia where the GST of 10% is not applied to basic, healthy foods [22,23,24,25], application of the Aboriginal and Torres Strait Islander Healthy Diets ASAP methods in remote Aboriginal communities showed that a healthy diet ($AUD827.63) was less expensive than the current diet ($AUD1,023.16) per household per fortnight. However, at 76% of the cost of the current diet, a healthy diet was potentially more affordable in the remote Aboriginal communities studied than in other places, where the cost of the healthy diet ranges between 80–85% [22,23,24,25]. Surprisingly, this price differential between the current and healthy diets was larger than in other studies even though alcohol was not included in the current diet, as the communities are ‘dry’ and alcohol is not available for sale.…”
Section: Discussionsupporting
confidence: 67%
“…This allows for comparison of diet price and affordability in specific population groups and locations with that of the general population, to inform the development of targeted health and fiscal policies. For example, in Australia, the Healthy Diets ASAP approach has been applied in country Victoria, as reported elsewhere in this special edition [25]. As another example, the INFORMAS ‘optimal’ approach to assessing diet price and affordability has been tailored to different population groups in New Zealand [26]; results showed that a healthy diet would be more affordable than the current diet for both the total New Zealand population (3.5% difference) and Pacific households (4.5% difference) but the cost of both diets would be similar for Māori households (0.57% difference).…”
Section: Introductionmentioning
confidence: 99%
“…There is a key role for academia to provide the evidence base and independent voice to inform and evaluate policy and programs and to challenge existing paradigms and assumptions. The International Journal of Environmental Research and Public Health Special Issue on Addressing Food Insecurity in Developed Countries is a good example of how the research community can come together to provide evidence to guide policy and practice [66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86]. There are many opportunities for academics to partner with government, industry, and the third sector to translate research to practice to improve the lives of people rendered food insecure in rich nations.…”
Section: What Should or Could Be Done And By Whommentioning
confidence: 99%
“…The two most commonly researched aspects of the consumer food environment were price (16 studies) [22,31,32,33,34,35,36,37,38,41,42,43,44,45,52,54] and available healthy options (15 studies) [31,32,33,36,40,43,44,45,46,47,48,49,50,52,54], supporting the findings of Glanz et al [10]. The next most commonly researched aspect was quality (10 studies) [22,31,32,33,36,43,44,45,46,51]; with promotion, placement and nutritional information researched by three studies [31,32,52] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Within this review, the most common method to collect food pricing information was through a ‘healthy food basket’ using a pre-defined list of foods in quantities representative of the total diet of referent families over a defined period of time. Six different healthy food basket methodologies were used: the Victorian Healthy Food Basket (VHFB) [37,41,42]; the Queensland Healthy Food Access Basket (QLD HFAB) [38], also used as the basis for the Western Australian tool [22]; a healthy food basket for New Zealand [54]; a pilot tool tested in rural and urban Tasmania [43]; and the Healthy Diets Australian Standardised Affordability and Price (ASAP) tool [35]. All food pricing studies using a healthy food basket methodology were from Australia and New Zealand.…”
Section: Resultsmentioning
confidence: 99%